Optimizing Road Pavement Projects Through Earned Value Concepts - Jufriza, Jufriza; Alkhaly, Yulius Rief; Jalil, Abdul (International Journal of Engineering, Science and Information Technology, 2024)
Every construction project faces constraints of cost, schedule, and quality that must be managed to achieve the desired objectives. This research aims to control the aspects of time and cost in construction projects by applying the Earned Value Concept and Crash Program methods. The subject of the study is the Preservation of Roads and Bridges project in Bireuen City - BTS, Lhokseumawe/Aceh Utara, Krueng Mane Buket Rata, SP. Krueng Geukeueh - PEL. Krueng Geukeueh (PEL. Lhokseumawe). The data analyzed includes the Budget Plan (RAB), project schedule, and reports on planned and actual work. This data is processed into three main indicators: BCWS, BCWP, and ACWP, which are then analyzed through Schedule Variance (SV), Cost Variance (CV), Schedule Performance Index (SPI), and Cost Performance Index (CPI). The analysis results show that during weeks 22 to 23, the project had a positive Schedule Variance (SV) (0), which then turned negative during weeks 24 to 28, with an average Schedule Performance Index (SPI) of 1.0096, indicating that project execution was ahead of schedule. Meanwhile, the Cost Variance (CV) was positive throughout the project, and the average Cost Performance Index (CPI) was 1.2118, indicating that actual costs did not exceed the budget. The application of the Crash Program method resulted in changes in heavy equipment rental costs and worker wages, from IDR 1,440,469,946.99 over 50 days to IDR 1,853,072,988.06 over 25 days, with a cost increase of IDR 412,603,041.07 and an acceleration ratio of 1.29. This research demonstrates that the Earned Value Concept and Crash Program methods are effective in controlling time and cost in construction projects, thereby helping to achieve better efficiency in project management.